The Relationship between Cash Flow Sensitivity of Investment with Level of Capital Expenditure M - Mahdi Sadidi; Ahmad Mohamadi Saniani (مطالعات تجربی حسابداری مالی, 2013)
The goal of this paper is to study of Relationship between cash flow sensitivity of investment with capital expenditure..the sample has been divided into two parts, over investment and under investment companies with using measure of investment mean and shown that the cash flow sensitivity of investment in over investment companies is greater than under investment companies .also Positive relationship have been shown between market to book ratio and capital expenditure. Also by using multiple measure (ratio of dividend, size and KZ index) representative of financial constraints, we understand that positive relationship is exist between cash flow sensitivity of investment with dividend ratio and size and negative relationship is exist between cash flow sensitivity of investment and KZ index.